Oxidação de arsênio via processo de fotocatálise heterogênea - Seára, Eriton Cácio Rufino (2016)
Contamination of water by inorganic arsenic and its compounds is a serious environmental problem in different regions of Brazil and the world. The main sources of contamination can come from both natural forms, from the geological formation of rocks, and anthropic form, from activities such as mining. Several regions in Brazil and in the world have surface water or groundwater with a total arsenic concentration higher than permitted by international law. Human poisoning by arsenic can lead to death or lead to numerous chronic or acute diseases. Ordinance 518/2004 - Ministry of Health) and (Resolution 357/2005 - CONAMA) establishes a maximum concentration of 10 μg L-1 for drinking water. Thus, this work aims to study the oxidation process via heterogeneous photocatalysis and subsequent removal via addition of precipitant. The photocatalysis experiments showed little or no influence of the pH in the total oxidative efficiency, in parallel, the removal by adsorption of As (III) in the catalyst shown to be ineffective for low catalyst masses, which is in agreement with data found in the literature. The results in this work also showed that the photolysis obtained very good oxidative efficiency, reaching 88.5% oxidation, in contrast to photocatalysis efficiencies of 93.2%, 93.5%, 95.0%, and 98.5% for the respective concentrations of 0.1, 0.5, 1.0 and 2.0 g L-1 of TiO2. The different forms of TiO2 were also tested and showed very close final oxidation efficiency, with a difference of 6.7% of rutile TiO2, calcined at 350C, front to commercial version, without calcination, as received. In the tests of recycle of the catalyst mass, it is possible to observe and influence of the generation and saturation of As(V) in the suspension, which in addition is acidified and has oxidative loss from 93% to 50% in four reuses of the same catalyst mass. Similarly, the photolysis cycles showed a loss of 89.2% to 29.5% of oxidative efficiency, as well as acidification of the system due to saturation of As(V) species in the medium. Finally, the experiments of removal of arsenic previously oxidized by precipitation with FeCl3 were very effective, providing a total residual arsenic concentration below the legislation, with the addition of less than 4 mg L-1 of precipitating agent. These results provide a better understanding of arsenic photo oxidative process, applied in water decontamination.